A rich and diverse tanaidomorphan (Crustacea: Tanaidacea) assemblage associated with Early Cretaceous resin-producing forests in North Iberia: palaeobiological implications - Sánchez-García, A; Peñalver, E; Pérez-De La Fuente, R; Delclòs, X (Taylor and Francis, 2014)
The extinct tanaidomorphan diversity from Early Cretaceous Spanish amber, currently comprising 26 specimens, is reassessed. The fossil family Alavatanaidae Vonk and Schram, 2007, described from Spanish amber, is revised on account of new preparation of type specimens and the discovery of new material. The described tanaidomorphan taxa are classified within the superfamily Paratanaoidea. An emended diagnosis for Alavatanaidae is provided, as well as for the genera Alavatanais Vonk and Schram, 2007 and Proleptochelia Vonk and Schram, 2007, and their respective species Alavatanais carabe Vonk and Schram, 2007 and Proleptochelia tenuissima Vonk and Schram, 2007. Three new species, two of them classified in a new genus each, are described: Alavatanais margulisae Sánchez-García, Peñalver and Delclòs sp. nov., Eurotanais terminator Sánchez-García, Peñalver and Delclòs gen. et sp. nov. and Electrotanais monolithus Sánchez-García, Peñalver and Delclòs gen. et sp. nov. Proleptochelia euskadiensis Vonk and Schram, 2007 is considered a junior synonym of A. carabe, and the genus Proleptochelia, together with its type and only species P. tenuissima, is left without familial placement within Paratanaoidea. Within this superfamily, Alavatanaidae is closely related to Leptocheliidae. Also, morphological variability due to sexual dimorphism in the studied paratanaoids has been determined. Multiple lines of taphonomic and palaeobiological evidence indicate that the Spanish amber tanaids were most likely inhabitants of wet or moist forest floors.